IMPLEMENTASI PERATURAN DAERAH NOMOR 9 TAHUN 2011 TENTANG PENGATURAN LALU LINTAS YANG BERSIFAT PERINTAH, LARANGAN DAN PETUNJUK PADA RUAS JALAN DI KABUPATEN SIAK - Budianto, Eko; Tua R.F.S, Harapan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Determination of Regional Regulation No. 9 of 2011 on traffic arrangements that are commands, prohibitions and instructions on the roads is a safeguard for the public against risks inflicted due to accidents, traffic awareness and reduce the death rate from traffic accidents. The Regulation aims to Siak district government could more forcefully to improve facilities and infrastructures as well as completing the road markings, as well as running a firm sanctions on driver and riders who likes violating traffic signs or road markings. In fact this regulation after enactment has not made a significant impact even in the last four years the number of accidents is increasing in Siak. It can be seen from report of the Siak Police Departement from year to year. The purpose of this study to analyze implementation of traffic management that are commands, prohibitions and directions on roads in Siak and to know the factors that influence it. This study uses qualitative descriptive methods, data collection techniques by observation and interviews in which the parties involved in the implementation of the policy as an informant. Research using the theory of Van Meter Van Horn. These results indicate that the implementation of traffic management that are commands, prohibitions and directions on roads in Siak has not run optimally due to awareness and society comprehension will a traffic and safety sorely lacking, as evidenced by the many people who commit violations annually and also causes them to lose their lives. That factors become an obstacle in the implementation is the lack of action that makes a deterrent effect on the society, lack of driving directions, and public awareness is still lacking in safety.Keywords : Implementation, Traffic, Road Marking